SIKAP DAN PENGAMBILAN KEPUTUSAN KONSUMEN DALAM MEMBELI AYAM POTONG DI KOTA BANDAR LAMPUNG - Wulan Juwita Sianturi; Ali Ibrahim Hasyim; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
The objectives of this research were to analyze: consumer attitudes, the stages of the purchase decision making, and the factors that affected the purchase decisions of chicken meat in Bandar Lampung City.  This research was conducted at three traditional markets in Bandar Lampung City, namely Tugu Market, SMEP Market, and Gintung Market. This  research was  a survey method, in which locations were determined on purpose, while the samples of 90 people were obtained by using accidental sampling technique. The data were analyzed by using descriptive qualitative analysis, multiatribute Fishbein analysis and logit regression analysis.  The results showed that consumer attitudes toward the attributes of chicken meat were that they preferred ‘ras’ chicken meat than kampong chicken meat; particularly in terms of the meat price and weight.  Consumer’s decision making stages of chicken meat showed that they bought chicken because of their awareness on the need of protein and 60 percent of them preferred to buy ‘ras’ chicken meat than kampong chicken meat.  Most consumers (61.11%) got information about chicken meat from merchants. There were 78 percent of consumers that were satisfied with their purchased of chicken meat and 12 percent were dissatisfied for getting improper weight and receiving unfresh meat. Factors that affected the purchase decisions of chicken meat in Bandar Lampung City were the price of ‘ras’ chicken meat protein, of kampong chicken meat, of salted fish, and family income.Key words: attitude, attribute, decision making